Degrading habitats and the effect of topographic complexity on risk assessment. Issue 12 (30th September 2013) - McCormick, Mark I.; Lönnstedt, Oona M.
Abstract: Topographic complexity is a key component of habitats that influences communities by modulating the interactions among individuals that drive population processes such as recruitment, competition, and predation. A broad range of disturbance agents affect biological communities indirectly through their modifications to habitat complexity. Individuals that best judge the threat of predation within their environment and can trade‐off vigilance against behaviors that promote growth will be rewarded with the highest fitness. This study experimentally examined whether topographic habitat complexity affected the way a damselfish assessed predation risk using olfactory, visual, or combined cues. Fish had higher feeding rates in the low complexity environment. In a low complexity environment, damage‐released olfactory cues and visual cues of predators complemented each other in the prey's assessment of risk. However, where complexity was high and visual cues obscured, prey had lower feeding rates and relied more heavily on olfactory cues for risk assessment. Overall, fish appear to be more conservative in the high complexity treatment. Low complexity promoted extremes of behavior, with higher foraging activity but a greater response to predation threats compared with the high complexity treatment. The degree of flexibility that individuals and species have in their ability to adjust the balance of senses used in risk assessment will determine the extent to which organisms will tolerate modifications to their habitat through disturbance. Abstract : Topographic complexity is a key component of habitats that influences communities by modulating the interactions among individuals that drive population processes such as recruitment, competition, and predation. This study experimentally examined whether topographic habitat complexity affected the way a damselfish assessed predation risk using olfactory, visual, or combined cues. The degree of flexibility that individuals and species have in their ability to adjust the balance of senses used in risk assessment will determine the extent to which organisms will tolerate modifications to their habitat through disturbance.